2023
DOI: 10.1590/fst.101422
|View full text |Cite
|
Sign up to set email alerts
|

Research Progress on the effect of Bacillus on flavor substances of Maotai flavor Baijiu

Abstract: The brewing of Chinese Baijiu is a microbial community fermentation system, in which there is a close and complex relationship between microorganisms and flavor quality, but the specific deep-seated mechanism still needs to be explored and interpreted continuously so far. In this review, Maotai flavor Baijiu was briefly introduced, and the microorganisms mainly affected by flavor substances, the main components of flavor substances, the factors affecting flavor formation and the application ways of functional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…In this study, we found that the accumulation of methanol during pit fermentation was mainly through the degradation of pectin and the hydrolysis of methyl acetate. Previous studies showed that Bacillus is an important component of the bacterial community of fermented grains, with the ability to utilize polysaccharides and metabolic flavor substances [40,41] and to degrade pectin [42]. In addition, during brewing and in the presence of the starter culture of fermented grains Daqu, there were many strains of Penicillium and Aspergillus with strong pectinase activity [43,44].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we found that the accumulation of methanol during pit fermentation was mainly through the degradation of pectin and the hydrolysis of methyl acetate. Previous studies showed that Bacillus is an important component of the bacterial community of fermented grains, with the ability to utilize polysaccharides and metabolic flavor substances [40,41] and to degrade pectin [42]. In addition, during brewing and in the presence of the starter culture of fermented grains Daqu, there were many strains of Penicillium and Aspergillus with strong pectinase activity [43,44].…”
Section: Discussionmentioning
confidence: 99%